A measurement method of motion parameters in aircraft ground tests using computer vision. (April 2021) - Cui, Jiashan; Li, Yunhui; Huo, Ju; Yang, Ming; Wang, Yongkun; Li, Cong
Highlights: A new method of motion parameters measurement in ground test of complex aircraft based on vector is presented. Detailed analysis of error transfer in pose measurement is given. Compared with binocular stereo vision, the accuracy of attitude angle measurement is improved by 100%. Abstract: The purpose of this work is aiming at the problem of high precision and large-scale measurement of motion parameters of aircraft ground test. Based on the traditional vision measurement method of motion parameters, a new measurement method of motion parameters based on intersected planes is discussed. Firstly, the measurement of 3D coordinates of laser spots was performed using the 3 D vision technique combined with plane constraints of curtain wall, the images of laser spot projected on the parallel curtain wall were processed using the centroid method, the calibration of multi-coordinates were unified by the unique coordinate system method, then the pose was solved using the proposed method that the normal vector of the intersect plane fixed on the vehicle is used. Finally, according to the measurement principle, the influence of spot center positioning, camera parameter calibration and target geometric error on the calculation results of aircraft motion parameters is analyzed, and the error propagation model is given. The experimental results show that in the measurement range of 8000 mm × 4000 mm × 4000 mm, the measurement error of attitude parameters is less than 0.14°, and the measurement error of position parameters is less than 2 mm. Compared with binocular stereo vision, the accuracy of attitude angle measurement is improved by 100%. Therefore, the measurement method proposed in this paper can achieve high precision and large-scale measurement of the motion parameters of the test aircraft.